In Harm's Way? Payday Loan Access and Military Personnel Performance - Carrell, Scott; Zinman, Jonathan (Review of Financial Studies, 2014)
Does borrowing at 400% APR do more harm than good? The U.S. Department of Defense thinks so and successfully lobbied for a 36% APR cap on loans to servicemen. But existing evidence on how access to high-interest debt affects borrowers is inconclusive. We estimate effects of payday loan access on enlisted personnel using exogenous variation in Air Force rules assigning personnel to bases across the United States, and within-state variation in lending laws over time. Airmen job performance and retention declines with payday loan access, and severely poor readiness increases. These effects are strongest among relatively inexperienced and financially unsophisticated airmen.